Evaluasi Kinerja Stgruktur Gedung BPJS Kesehatan Cabang Ambon Terhadap Gempa Dengan Metode Pushover - Vector R. R. Hutubessy (Jurusan Teknik Sipil, 2022)
On September 26th 2019, an earthquake of 6.5 SR hit Kairatu, West Seram. Since West Seram is close to Ambon, the earthquake was greatly felt as well. Many people were panicked and run out from their houses and several buildings were severely damaged, including the MIPA building of Unpatti, the Medicine building Unpatti and the building of BPJS Kesehatan. Therefore, it is a must to understand that the structure evaluation of certain building is highly needed in order to understand the building that we own. The improvement of science and technology has greatly helped the world of civil engineering in planning and analyzing the performance of certain building in order to do the Structure Evaluation of the building of BPJS Kesehatan Ambon towards the Earthquake using Pushover Method. The static non-liner analysis with the use of Pushover analysis method showed that a building could only hold the earthquake of 615,53 ton. Reviewed based on the C. F. Ritcher scale, that worth is on 4 – 4.9 (magnitude which is in light category. The limit of the roof drift ratio is obtained by a maximum total drift of 0.000647 while the maximum in-elastic drift is -0.00026 and is included in the Immediate Occupancy (IO) performance level, the effective base shear force in a linear state is smaller than the design base shear value (V = 71.085 < V plan 115.464 tons. It is shown that the structure could be non-linear when the collapse happened.Keyword: Pushover Analysis, Level of Performance, Shearing Stress